2012
DOI: 10.1111/j.1559-1816.2012.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between the Theory of Planned Behavior and the Value–Belief–Norm Model Regarding the Environment, on Spanish Housewives' Recycling Behavior

Abstract: Environmental behaviors have been analyzed from different theoretical models. The theory of planned behavior emphasizes the attitudinal aspects associated with behavior, while the value–belief–norm model regarding the environment focuses on the importance of moral components when setting environmental behaviors in motion. The objective of this study was to analyze both models, comparing both their degree of fit and their predictive power regarding recycling behavior. To do so, we used a sample made up of 154 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 76 publications
2
68
1
8
Order By: Relevance
“…The TPB and related constructs have been used in the prediction of many behaviors (e.g., Ajzen, 2001;Ajzen & Fishbein, 1980;Armitage & Conner, 2001), including a plethora of ERB (e.g., Aguilar-Luzon, Garcia-Martinez, Calvo-Salguero, & Salinas, 2012;Bamberg, 2003;Bamberg & Moser, 2007;Chao, 2012;Fielding, McDonald, & Louis, 2008;Kaiser & Gutscher, 2003). For example, in a meta-analysis of research on a wide range of ERB Bamberg & Moser (2007) tested a theoretical model that integrated TPB variables with other variables.…”
Section: Tpb and Energy Conservationmentioning
confidence: 99%
“…The TPB and related constructs have been used in the prediction of many behaviors (e.g., Ajzen, 2001;Ajzen & Fishbein, 1980;Armitage & Conner, 2001), including a plethora of ERB (e.g., Aguilar-Luzon, Garcia-Martinez, Calvo-Salguero, & Salinas, 2012;Bamberg, 2003;Bamberg & Moser, 2007;Chao, 2012;Fielding, McDonald, & Louis, 2008;Kaiser & Gutscher, 2003). For example, in a meta-analysis of research on a wide range of ERB Bamberg & Moser (2007) tested a theoretical model that integrated TPB variables with other variables.…”
Section: Tpb and Energy Conservationmentioning
confidence: 99%
“…Perceived behavioural control is also considered a direct antecedent to behaviour, to the extent that it represents actual control. Our review of TPB studies when applied specifically to recycling found 24 independent papers (Aguilar-Luzón et al, 2012;Barr, 2007;Barr, Gilg, & Ford, 2001;Castro, Garrido, Reis, & Menezes, 2009;K. Chan, 1998;L.…”
mentioning
confidence: 99%
“…Both of these cars serve the same purpose; however, they appeal to consumers with different values, beliefs, and norms. Indeed, many studies have demonstrated the impacts of values, beliefs, and norms on various environmental behaviors (Stern and Dietz 1994;Stern et al 1999;Stern 2000;Nilsson et al 2004;Nordlund and Garvill 2002;Schultz et al 2005;Aguilar-Luzon et al 2012).…”
Section: Integrity Of Values Beliefs and Normsmentioning
confidence: 99%